Cyanobacteria: A Natural Source for Controlling Agricultural Plant Diseases Caused by Fungi and Oomycetes and Improving Plant Growth - Hillary Righini; Ornella Francioso; Antera Martel Quintana; Roberta Roberti (Horticulturae, 2022)
Cyanobacteria, also called blue-green algae, are a group of prokaryotic microorganisms largely distributed in both terrestrial and aquatic environments. They produce a wide range of bioactive compounds that are mostly used in cosmetics, animal feed and human food, nutraceutical and pharmaceutical industries, and the production of biofuels. Nowadays, the research concerning the use of cyanobacteria in agriculture has pointed out their potential as biofertilizers and as a source of bioactive compounds, such as phycobiliproteins, for plant pathogen control and as inducers of plant systemic resistance. The use of alternative products in place of synthetic ones for plant disease control is also encouraged by European Directive 2009/128/EC. The present up-to-date review gives an overall view of the recent results on the use of cyanobacteria for both their bioprotective effect against fungal and oomycete phytopathogens and their plant biostimulant properties. We highlight the need for considering several factors for a proper and sustainable management of agricultural crops, ranging from the mechanisms by which cyanobacteria reduce plant diseases and modulate plant resistance to the enhancement of plant growth.